Implementation of Corporate Social Responsibility Program Responsibility Program Im-plementation with The Triple Bottom Line Approach - Kamal, Iqbal; Rofiaty (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to evaluate the Corporate Social Responsibility (CSR) practices of PT Greenfields Indonesia Dairyfarm 1 Malang using the Triple Bottom Line (TBL) framework, focusing on the People, Planet, and Profit dimensions. Design/Methodology/Approach – This study employs a qualitative descriptive approach. Data were collected through interviews, observations, and documentation to assess the implementation of CSR practices based on the Triple Bottom Line framework. Findings – The results reveal that PT Greenfields has successfully implemented CSR initiatives across the People, Planet, and Profit dimensions. The People dimension includes contributions to community welfare, healthcare, education, and infrastructure; the Profit dimension focuses on community empowerment and partnerships in dairy farming and forage crop cultivation; and the Planet dimension involves environmental sustainability programs such as reforestation and greening initiatives. However, weaknesses remain in the People dimension, particularly in infrastructure development. Therefore, the study recommends enhancing supervision, strengthening collaboration with community leaders, expanding infrastructure-related CSR programs, and increasing community participation to improve CSR effectiveness and support long-term sustainability. Originality/Value This research provides value by offering a comprehensive assessment of CSR using the TBL framework in the dairy farming industry, identifying both strengths and gaps while presenting actionable recommendations that support long-term sustainability and community engagement.